Analysis of Financial Ratio on Financial Performance and Sustainability Report as Intervening Variable - Ni Nyoman Sawitri (Atestasi : Jurnal Ilmiah Akuntansi, 2023)
Study This aims to know and analyze the influence of Current Ratio (CR), Debt Equity Ratio (DER), Total Asset Turnover (TOTA), and Return on Assets (ROA) on Company Performance as proxied by Return on Equity (ROE) through Sustainability Report (SR) as variable intervening in the company cruise 2019-2021 period. Sample in the study: This consists of 5 companies in the cruise sector from 2019 to 2021. Study method This uses SEM PLS with SmartPLS programs and techniques, taking samples with purposive sampling. Result of study This shows that, in a way, Partial Ratio Finance that is proxied by Current Ratio (CR), Debt Equity Ratio (DER), Total Asset Turnover (TOTA), and Return on Assets (ROA) has an influence significant on Financial Performance as proxied by Return on Equity (ROE) and Sustainability Report (SR). Simultaneous results show that Ratio Finance that is proxied by Current Ratio (CR), Debt debt-equity ratio (DER), Total Asset Turnover (TOTA), and Return on Assets (ROA) have an influence significant on Financial Performance as proxied by Return on Equity (ROE) through Sustainability Report (SR) or mediated in a way complete with t- calculated value 2.533>1.96. As well as abilities variable independent in explaining variable dependent and variable intervening is by 87% and 69.1%. Meanwhile, the rest, 13 % and 30.9%, are defined by variables other independents outside the model.